A new subspecies of Trypanosoma cyclops found in the Australian terrestrial leech Chtonobdella bilineata. Issue 10 (12th September 2021) - Ellis, John; Barratt, Joel; Kaufer, Alexa; Pearn, Lauren; Armstrong, Brigette; Johnson, Michael; Park, Yasunori; Downey, Lara; Cao, Maisie; Neill, Levina; Lee, Rogan; Ellis, Bethany; et al.
Abstract: Abstract: Previously, it was suggested that haemadipsid leeches represent an important vector of trypanosomes amongst native animals in Australia. Consequently, Chtonobdella bilineata leeches were investigated for the presence of trypanosome species by polymerase chain reaction (PCR), DNA sequencing and in vitro isolation. Phylogenetic analysis ensued to further define the populations present. PCR targeting the 28S rDNA demonstrated that over 95% of C. bilineata contained trypanosomes; diversity profiling by deep amplicon sequencing of 18S rDNA indicated the presence of four different clusters related to the Trypanosoma ( Megatrypanum ) theileri . Novy–MacNeal–Nicolle slopes with liquid overlay were used to isolate trypanosomes into culture that proved similar in morphology to Trypanosoma cyclops in that they contained a large numbers of acidocalcisomes. Phylogeny of 18S rDNA/GAPDH/ND5 DNA sequences from primary cultures and subclones showed the trypanosomes were monophyletic, with T. cyclops as a sister group. Blood-meal analysis of leeches showed that leeches primarily contained blood from swamp wallaby ( Wallabia bicolour ), human ( Homo sapiens ) or horse ( Equus sp.). The leech C. bilineata is a host for at least five lineages of Trypanosoma sp. and these are monophyletic with T. cyclops ; we propose Trypanosoma cyclops australiensis as a subspecies of T. cyclops based on genetic similarity and biogeography considerations.